2005
DOI: 10.1111/j.1525-1497.2005.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac risk underestimation in urban, black women

Abstract: Background: Black women have a disproportionately higher incidence of cardiovascular disease mortality than other groups and the reason for this health disparity is incompletely understood. Underestimation of personal cardiac risk may play a role. Objective: We investigated the personal characteristics associated with underestimating cardiovascular disease in black women. Design, Setting, Participants: Trained surveyors interviewed 128 black women during the baseline evaluation for a randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 33 publications
(53 reference statements)
1
27
0
Order By: Relevance
“…16 In addition, a lack of awareness of heart disease risk factors translates into an underestimation of risk in both urban and racial minority women. 32 Unlike previous studies assessing differences in knowledge and awareness of heart disease in subgroups of women, 28,33,34 we also developed and assessed a pre-/posteducational intervention. Our intervention differed from others in that it was designed to be delivered in the clinic setting by busy healthcare professionals and within the context of a clinical visit.…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, a lack of awareness of heart disease risk factors translates into an underestimation of risk in both urban and racial minority women. 32 Unlike previous studies assessing differences in knowledge and awareness of heart disease in subgroups of women, 28,33,34 we also developed and assessed a pre-/posteducational intervention. Our intervention differed from others in that it was designed to be delivered in the clinic setting by busy healthcare professionals and within the context of a clinical visit.…”
Section: Discussionmentioning
confidence: 99%
“…SRH is based on a single question asking people to rate their overall health status and has been shown to be reliable measure of individuals’ subjective health [6, 7]. According to previous survey results, the prevalence of good SRH varied greatly and was more prevalent among men in countries like Austria, France, Latvia, Norway, Poland, Russia, Armenia as well as in Estonia [813] but among women in Finland, Ireland and Great Britain [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Woodard and colleagues (2005) found that African Americans demonstrated less knowledge regarding risk factors for cardiovascular disease, compared to Caucasians. The lesser knowledge that African Americans demonstrated regarding risk factors of cardiovascular disease may directly correlate with the finding that African American women with multiple cardiac risk factors underestimated their risk for heart disease [5]. Furthermore, Mosca and colleagues (2000) surveyed over 1,000 women and found that only 8% recognized CHD or stroke as their greatest health concern and less than one-third identified CHD as a leading cause of death.…”
Section: Introductionmentioning
confidence: 99%